Attribution of 12 high-risk human papillomavirus genotypes to infection and cervical disease (2014)
Background: We estimated the prevalence and incidence of 14 human papillomavirus (HPV) types (6/11/ 16/18/31/33/35/39/45/51/52/56/58/59) in cervicovaginal swabs, and the attribution of these HPV types in cervical intraepithelial neoplasia (CIN), and adenocarcinoma in situ (AIS), using predefined algorithms that adjusted for multiple-type infected lesions. Methods: A total of 10,656 women ages 15 to 26 years and 1,858 women ages 24 to 45 years were enrolled in the placebo arms of one of three clinical trials of a quadrivalent HPV vaccine. We estimated the cumulative incidence of persistent infection and the proportion of CIN/AIS attributable to individual carcinogenic HPV genotypes, as well as the proportion of CIN/AIS lesions potentially preventable by a prophylactic 9-valent HPV6/11/16/18/31/33/45/52/58 vaccine. Results: The cumulative incidence of persistent infection with?1 of the seven high-risk types included in the 9-valent vaccine was 29%, 12%, and6%forwomen ages 15 to 26, 24 to 34, and 35 to 45 years, respectively.Atotal of 2,507 lesions were diagnosed as CIN or AIS by an expert pathology panel. After adjusting for multiple-type infected lesions, amongwomen ages 15 to 45 years, these seven high-risk types were attributed to 43% to 55% of CIN1, 70% to 78% of CIN2, 85% to 91% of CIN3, and 95% to 100% of AIS lesions, respectively. The other tested types (HPV35/39/51/56/59) were attributed to 23% to 30% of CIN1, 7% to 14% of CIN2, 3% to 4% of CIN3, and 0% of AIS lesions, respectively. Conclusions: Approximately 85% or more of CIN3/AIS, >70% CIN2, and approximately 50% of CIN1 lesions worldwide are attributed to HPV6/11/16/18/31/33/45/52/58. Impact: If 9-valent HPV vaccination programs are effectively implemented, the majority of CIN2 and CIN3 lesions worldwide could be prevented, in addition to approximately one-half of CIN1.